Protocols for Reporting Speech Outcomes following Palatoplasty or Velopharyngeal Surgery: A Literature Review. Issue 2 (February 2019) - Kummer, Ann W.; Hosseinabad, Hedieh Hashemi; Redle, Erin; Clark, Stacey
Abstract : Background: To determine best practices, surgeons who perform cleft palate surgery or surgery for velopharyngeal insufficiency need to be able to compare their outcomes in normalizing the velopharyngeal valve. Methods: We conducted a comprehensive review of articles that reported speech/resonance outcomes following palatoplasty or surgery for velopharyngeal insufficiency. We analyzed protocols that were used and how the results were reported. We found 170 articles, published between 1990 and 2014, that met our inclusion criteria. Results: Most studies (66%) had a sample size of <50 subjects, were retrospective (67%), were not blinded (83%), and did not report the use of reliability (68%). Most studies included 1 evaluator (27%) or 2 evaluators (30%). Only 80% of the articles specified that at least one speech pathologist was an evaluator. Most articles (56%) did not specify the speech samples used, and 65% used an informal test or did not specify the type of test used. Most studies used a perceptual rating scale for articulation (75%) and resonance (83%). Only 39% of the studies included an evaluation of velopharyngeal function. Finally, objective measures were used in only 28% of the studies (9% used aerodynamic measures and 19% used nasometry). Conclusions: Because these articles showed significant variability in how speech/resonance is evaluated and how the outcomes are reported, it is virtually impossible to compare results to determine best surgical procedures. Suggestions are given to standardize outcome measures to improve comparability of data.